Effects of a Potentiation Method of Resisted Sled Sprint Training On Mechanical Sprint Performance in Young Soccer Players - Soufiane, ZAHIDI; BRAHAM Mounir, AIT ALI (Journal of Sport Science Technology and Physical Activities, 2022)
This study compared the effects of two training sessions with a resistance sled, weighing ±15 % of the subject's mass, on the acceleration and maximum speed of young footballers (N = 16). the players on were randomly divided into three groups, a control group (C), a group carrying out combined training (C + S) or carrying out training with a sled only (CH). The training program consists on two sprint workouts per week for four weeks. Following the programs, the C + S and CH groups had significant gains on 0-30 (p = 0.02) and (p = 0.04) respectively. The CH group also had a significant gain on 0-20 (p = 0.04). Without further improvement of the other groups. To conclude, the method with the sled alone seems to allow the best performance